Organic chemistry - Solomons, T. W. Graham; Fryhle, Craig B. (New York : Wiley, 2000)
On the cover of this book is a Pacific yew tree, found in the ancient forests of the Pacific Northwest. The bark of the Pacific yew tree produces Taxol, found to be a highly effective drug against ovarian and breast cancer. Taxol blocks mitosis during eukaryotic cell division. The supply of Taxol from the Pacific yew tree is vanishingly small, however. A single 100-year-old tree provides only about one dose of the drug (roughly 300 mg). For this reason, as well as the spectacular molecular architecture of Taxol, synthetic organic chemists fiercely undertook efforts to synthesize it. Five total syntheses of Taxol have thus far been reported. Now, a combination of isolation of a related metabolite from European yew needles, and synthesis of Taxol from that intermediate, supply the clinical demand. This case clearly demonstrates the importance of synthesis and the use of organic chemistry. It's just one of the many examples used in the text that will spark the interest of students and get them involved in the study of organic chemistry!
Carbon compounds and chemical bonds -- Representative carbon compounds: funtional groups, intermolecular forces, and infrared (IR) spectroscopy -- An introduction to organic reactions: acids and bases -- Alkanes: nomenclature, conformational analysis, and an introduction to synthesis -- Stereochemistry: chiral molecules -- Ionic reactions--nucleophilic substitution and elimination reactions of alkyl halides -- Alkenes and alkynes I: properties and synthesis. Elimination reactions of alkyl halides -- Alkenes and alkynes II: addition reactions -- Nuclear magnetic resonance and mass spectrometry: tools for structure determination -- Radical reactions -- Alcohols and ethers -- Alcohols from carbonyl compounds. Oxidation--reduction and organometallic compounds -- Conjugated unsaturated systems -- Aromatic compounds -- Reactions of aromatic compounds. Aldehydes and ketones I: nucleophilic addition to the carbonyl group -- Aldehydes and ketones II. aldol reactions -- Carboxylic acids and their derivatives. Nucleophilic addition-elimination at the acyl carbon -- Synthesis and reactions of B-dicarbonyl compounds: more chemistry of enolate ions -- Amines -- Phenols and aryl halides: nucleopholic aromatic substitution -- Carbohydrates -- Lipids -- Amino acids and proteins -- Nucleic acids and protein synthesis.
Includes bibliographical references and index.
Keywords: CHEMISTRY, ORGANIC